Cover Feature: Isolable 1‐Butene Copper(I) Complexes and 1‐Butene/Butane Separation Using Structurally Adaptable Copper Pyrazolates (3/2021). Issue 3 (22nd January 2021) - Elashkar, Ahmed H.; Parasar, Devaborniny; Muñoz‐Castro, Alvaro; Doherty, Cara M.; Cowan, Matthew G.; Rasika Dias, H. V.
Abstract : The Cover Feature shows that 1‐butene molecules can penetrate into a dense crystalline solid and drive the transformation of planar trinuclear fluorinated copper(I) pyrazolate complexes toward boat‐shaped, dinuclear copper‐butene adducts. The chemistry of these complexes with 1‐butene is also examined in solution, and a comparison with analogous adducts formed with ethene and propene is provided. More information can be found in the Full Paper by M. G. Cowan, H. V. Rasika Dias, and co‐workers .